Economic assessment of the environmental services of PNA Cerro Mohinora, Guadalupe y Calvo, Chihuahua - García García, Samuel Alberto; Alanís Rodríguez, Eduardo; Aguirre Calderón, Oscar Alberto; Yerena Yamallel, José I.; CUÉLLAR-RODRÍGUEZ, Luis G.; Alejandro Collantes Chávez, Alejandro; Rascón Solano, Joel (Academic Press, 2023)
The Cerro Mohinora Protected Natural Area (PNA) located in Guadalupe y Calvo, Chihuahua, Mexico has ecosystems in a good state of conservation that include trees of genera such as Picea, Abies and Pseudotsuga. The objective was to determine the willingness to pay (WTP) by the visitors through the Contingent Valuation Method (CVM) in order to conserve the environmental services (SA) provided by the area and to know their perception of the current state of the Hill. 210 surveys were carried out to simulate a hypothetical market, where they asked what is the maximum amount they would be willing to pay to preserve and/or improve the SA of the PNA. The main results show that 90.48% of the visitors gave a positive WTP, 48.57% of the visitors are local and 55.24% have a university degree. 60.48% of the visitors do ecotourism on the Hill. The main suggestion to improve the area was the maintenance of the roads (55.00%) and the provision of more environmental education (32.69%). The only variable that influenced a positive WTP and that was statistically significant was the “Perception of good ecosystem quality (PGEQ)”. The average WTP calculated was 90.48 MXN, with a minimum and maximum of 68.12 MXN and 97.60 MXN, respectively, and a standard deviation of 5.55 MXN. The WTP should be established according to the number of visitors and use of the place, considering that it currently has no cost and that most visitors are willing to pay to enter and show concern for conservation.